Computer Modellig оf the Local Distortions of Geometric Shape of One-Layer Lattice Domes - E V Lebed; A V Atkin (RUDN Journal of Engineering Research, 2012)
Solution of the problem of modeling the local distortions of geometric shape of one-layer domes and its program implementation are presented in the paper. Modeling is based on selection of nodes on the computer screen and assigning the values of initial deviations of selected nodes from the ideal surface along the normal to this surface. The graphical user interface of the program includes the necessary set of instruments and the color palette of visualization for the pattern of distortion.